Sister-City Relationships As a Form of Inter-Organizational Cooperation: Exploratory Case Studies in the Portuguese Context - Mário FRANCO; Elsa MARMELO (Transylvanian Review of Administrative Sciences, 2014)
The aim of this study is to identify, characterize and understand sister-city relationships in Portuguese municipalities as a particular form of inter-organizational cooperation. There is however a great lack of research on this phenomenon, and a study on this subject was therefore carried out in three cities/municipalities. The instrument for data collection was the semi-structured interview with local authority representatives, and the data processing technique was content analysis. Based on the results obtained in this investigation, we can say that the kind of inter-organizational cooperation most widely used is sister-city relationships. Close relationships, friendship, exchange of experiences, sharing common needs, culture and economic interest are advantages achieved with this type of relationship between cities. The benefits allow better development of the municipalities involved. Some guidelines to be used as a basis for future research are also presented.